ILF2: a multifaceted regulator in malignant tumors and its prospects as a biomarker and therapeutic target - Sun, Tonglin; Li, Xi; Zhang, Yi; Zou, Bingwen; Zhang, Yan (Frontiers in Oncology, 2024)
Interleukin enhancer binding factor 2 (ILF2), formerly called nuclear factor 45 (NF45), is widely expressed in normal human tissues. ILF2 often binds to interleukin enhancer binding factor 3 (ILF3) and regulates gene expression in several ways, participating in multiple DNA and RNA metabolism pathways. Recent studies have shown that ILF2 expression is significantly upregulated in esophageal cancer, lung cancer, gastric cancer, and other malignant tumors, which can promote tumor development and tumor cell proliferation, affect the cell cycle, and induce epithelial-mesenchymal transition. ILF2 expression is closely related to tumor cell migration and invasion, neo-angiogenesis, and patient prognosis. ILF2 is expected to become a biomarker for the early diagnosis of patients with tumors and assessing their prognosis. This article reviews the role of ILF2 in malignant tumors and its related mechanisms.